A review of Q fever in Australia 1991-1994 - Michael G. Garner; Helen M. Longbottom; Robert M. Cannon; Aileen J. Plant (Elsevier, 1997)
Abstract: Q fever continues to be an important disease in Australia. Despite the development of an effective vaccine that has been commercially available since 1989, the number of cases notified has continued to increase. This study reviewed national notifications of Q fever between 1991 and 1994, togetherwith demographic, socioeconomic and occupational information, to investigate temporal and spatial disease patterns. Based on notification data, Q fever can be considered primarily a disease of adult males that occurs in eastern Australia: southern Queensland and northern New South Wales have the highest levels of activity. A significant association between Q fever activity of areas and the presence of livestock was found. A strong association with the meat industry was also confirmed. Q fever is conservatively estimated to cost Australia around A $1 million and more than 1700 weeks of work time annually. There is a need to increase awareness of this disease and its prevention. An extension program in rural communities and provision of vaccine to all abattoir workers would appear to be sensible public health approaches